Metabolic factors contribute to T‐cell inhibition in the ovarian cancer ascites. Issue 7 (25th April 2020) - Gong, Yueqing; Yang, Jianling; Wang, Yan; Xue, Lixiang; Wang, Junjie
Abstract : Malignant ascites is one of the major clinical features of ovarian cancer, which serves as a carrier for the peritoneal dissemination of tumor cells and predicts a poor prognosis in patients. In the microenvironment of ovarian cancer ascites, antitumor immunity is suppressed, which enables the tumor cells to escape from immune surveillance. The metabolic factors, including hypoxia, nutrient deprivation and accumulation of metabolic products, contribute to the immunosuppressive status of malignant ascites. The malignant ascites and ovarian solid tumors exhibit differential metabolic profiles. In this review, we have summarized the most recent findings on the interaction between immune cells and metabolic factors in the ovarian cancer ascites. The effects of metabolic factors on the antitumor functions of T‐cells in the malignant ascites were analyzed. Finally, we have discussed the potential directions for future research in this field.